The political system of the European Union and the politological and political determinants of the activity of the EU Council and the European Council - Czachór, Zbigniew (Wydział Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2019)
If the relationship between the EU Council and the European Council in the context of the horizontal division of power is based on a system of checks and balances, the emphasis must be on balance rather than on the separation of authorities/entities exercising power. For this reason, the powers and authority of the states and of the European Union are to some extent mixed up in this relational formula, and they overlap. At the same time, each entity has decision-making powers creating a mechanism of political influence. The powers of the EU Council and the European Council are separated in terms of institutions (structures and personnel) but not of functions, because their powers are interrelated. The competition for power here results in its being shared, which is based on the ‘joint exercising’ of power and thus the joint performance of certain systemic functions, tasks and roles. The powers of one authority should not be performed directly or completely by any of the remaining authorities, and none of the authorities should gain a definite advantage over the others. This should be the message for both the presidency of the EU Council and for the President of the European Council.

Jeżeli przyjąć, iż relacja Rada UE – Rada Europejska w kontekście poziomego podziału władzy opiera się na systemie checks and balances, czyli systemie „hamulców i równoważników”, nacisk musi zostać położony na równowagę, a nie oddzielenie władz/podmiotów ją wykonujących. Dlatego kompetencje i władza państwa i Unii Europejskiej są w formule tej relacji do pewnego stopnia wymieszane i nakładają się na siebie. Jednocześnie każdy z podmiotów dysponuje uprawnieniami decyzyjnymi, tworząc mechanizm politycznego oddziaływania. Władza Rady UE i Rady Europejskiej odseparowane są w sensie instytucjonalnym (strukturalnym i personalnym), ale nie funkcjonalnym, gdyż w rzeczywistości ich uprawnienia są ze sobą powiązane. Wynikiem konkurencji o władzę jest tu jej dzielenie, które opiera się na „wspólnym korzystaniu”, a więc łącznym wykonywaniu jej funkcji, zadań i ról. Uprawnienia jednej władzy nie powinny być bezpośrednio ani całkowicie wykonywane przez żadną z pozostałych władz i żadna z władz nie powinna uzyskać zdecydowanej przewagi nad innymi. To przesłanie towarzyszyć musi zarówno prezydencji Rady UE, jak i Przewodniczącemu Rady Europejskiej.
System polityczny Unii Europejskiej a politologiczne i polityczne uwarunkowania aktywności Rady UE i Rady Europejskiej
Keywords: Council of the EU; European Council; political system; politicization and democratization of the EU; political legitimization of authorities; priorities; penetration and permeation; Europeanization and internationalization; Rada UE; Rada Europejska; system polityczny; polityzacja i demokratyzacja UE; legitymizacja polityczna władzy; priorytety; penetracja i przenikanie; europeizacja i internacjonalizacja